2021
DOI: 10.46542/pe.2021.211.833837
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Google Classroom and Edmodo in online learning during the COVID-19 pandemic among pharmacy students of Health Polytechnic of Health Ministry Kupang, Indonesia

Abstract: Objective: This study aims to determine the effectiveness of using Google Classroom and Edmodo in online learning during the Covid-19 pandemic. Method: This research is quantitative research. The sample was pharmacy students of the Health Polytechnic of Ministry of Health in Kupang of 2019 and 2020 cohort, with a total of 145 people. Data were collected using a questionnaire. Results: One hundred and twelve (72%) students stated that the use of Google Classroom in online learning during the Covid-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The analysis of answers to question Q1 revealed that the majority of students preferred easy access from anywhere on Google Classroom, easy access to learning materials, and also appreciate the structure and the workflow provided by Google Classroom, which is in line with the findings of Tenda et al in [17] and Oktaria et al in [12].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The analysis of answers to question Q1 revealed that the majority of students preferred easy access from anywhere on Google Classroom, easy access to learning materials, and also appreciate the structure and the workflow provided by Google Classroom, which is in line with the findings of Tenda et al in [17] and Oktaria et al in [12].…”
Section: Discussionsupporting
confidence: 76%
“…It is also known to use high-speed internet connection intensively, so a poor quality internet connection will create a severe disadvantage for some students or teachers, although Google has tried to fix it [20]. Other limitations were shown in [17], where the research highlighted that Google Classroom's communication process between students and teachers was not optimal, and not at the last in [18] where it's shown that Google tracks students' and teachers' activity for advertising purposes. All of that can lead to a different degree of acceptance, efficiency, comfort, or usefulness, to increase stress levels besides those already caused by coronavirus [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Students show a response in learning mathematics with their behavior while still chatting outside the learning material. Students also feel happy when the teacher is absent (Khoiriyah et al, 2022;Tenda, 2021). Indicators include a feeling of liking or enjoyment in learning activities, a feeling of interest in learning, an awareness of learning without being asked, participating in learning activities, and paying attention to learning (Rahayu & Timur, 2020;Santiago et al, 2023).…”
Section: Introductionmentioning
confidence: 99%